ANALYSIS OF SPATIO-TEMPORAL PATTERNS OF HYDRO-GEOMORPHIC SENSITIVITY AREAS AND DESERTIFICATION STATUS IN A PART OF BORNO-YOBE SEMI-ARID ZONE OF NIGERIA - Ndabula, C.; Iguisi, E. O.; Jidauna, G. G.; Oyatayo, K.; Nyomo, D. J. (FUDMA JOURNAL OF SCIENCES, 2023)
The major goal of this study is to monitor spatio-temporal patterns of hydro-geomorphic sensitivity indicators to depict desertification status in the semi-arid zone of Nigeria over a period of 30 years (1987-2016).Four specific hydro-geomorphic indices; Topographic Wetness Index (TWI), Stream Power Index (SPI), Sediment Transport Index (STI) and Normalised Difference Water Index (NDWI), were evaluated and mapped into raster layers using appropriate algorithm on the Digital Elevation Model (DEM). These indicators represent soil moisture, surface run-off erosivity, soil erosion and surface water distribution respectively which represent the key hydro-geomorphic forms and processes of desertification. The MEDALUS (ESA) approach was applied to aggregate specific temporal indices into single component index; TWSI, SPSI, STSI NDWSI respectively and the four into the Hydro-geomorphic Sensitivity Index (HgSI). These respective indices were further segmented and mapped into five sensitivity areas and to determine their mean extents; Very High (VH), High (H), Moderate (M), Low (L) and Very Low (VL) based on natural jenks method. The five hydro-geomorphic sensitivity classes were validated based on post classification field reconnaissance to interpret the corresponding landscape as follows; Very High (upslope catchment area with sparse shrubs), High (upslope catchment area with patchy dense shrubs), Moderate (light riparian/woody savanna), Low (wetland/floodplain/dense woody savanna) and Very Low (Broad river/Water bodies/Oases) respectively. Results showed average extents of Hydro-geomorphic sensitivity classes for the 30373 km2 study area for the period as follows; VH: upslope catchment with sparse shrubs (6532 km2), H: upslope catchment with dense shrubs (11521 km2), M: Riparian/forest/woody savanna (5643 km2),